Radio-frequency thermal ablation of lung cancer under epidural anaesthesia: comparison of the effectiveness of blocks between higher and mid-thoracic level (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Purpose of the investigation is to evaluate the effectiveness of high thoracic epidural block in comparison to mid-thoracic epidural during Radiofrequency ablation for lung cancer. 60 patients (38 male) were selected for epidural segmental block who were proposed for radiofrequency thermal ablation for lung cancer. Patients were randomly divided in 2 groups: Group-A, higher thoracic epidural group & Group-B, mid-thoracic epidural group. Under all aseptic preparation 18 G Epidural catheter was inserted through 18 G epidural needle and 4-6 ml of 0.5% bupivacaine was used during anaesthesia. Extend of block was demarcated by pain prick. RFT probe was allowed to insert 30 minutes after anaesthesia. The heat rate, blood pressure, respiration, Sp02 and temperature were monitored continuously during the procedure. Excellent block was found in 21 cases of Group-A and 15 cases of Group-B. Anaesthesia was inadequate in two cases of Group-A, and in 5 cases of Group-B, So, Higher thoracic epidural technique is better than mid thoracic epidural.DOI: http://dx.doi.org/10.3329/jbsa.v17i1.4050 Journal of BSA, Vol. 17, No. 1 & 2, 2004 p.36-38